2015
DOI: 10.1590/s0100-736x2015000200009
|View full text |Cite
|
Sign up to set email alerts
|

Componentes principais das características de carcaças de bovinos anelorados e fontes de variação em lesões

Abstract: Objetivou-se levantar e avaliar os componentes principais das características de carcaças de bovinos anelorados e fontes de variação em lesões. Utilizou-se um banco de dados com informações de 15.002 carcaças de bovinos anelorados. As variáveis levantadas foram peso da carcaça quente, conformação da carcaça, escore de gordura subcutânea, condição sexual, número de dentes incisivos, lesões e distância percorrida da propriedade rural ao abatedouro. Também foi considerado o sistema de terminação dos bovinos por m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Uma forma mais acurada de estimar associações de variáveis que são correlacionadas, como é caso dos escores de EPM e as variáveis da carcaça (Tabela 3), é através de análises multivariadas (SILVA et al, 2015;FERREIRA et al, 2018;OLIVEIRA et al, 2019a;OLIVEIRA et al, 2019b). Esta ferramenta estatística pode ser usada com sucesso para apoiar a tomada de decisão na escolha de variáveis que efetivamente contribuem para a elucidação do caráter alvo, que nesse caso, é a precocidade em fêmeas da raça Nelore.…”
Section: Resultsunclassified
“…Uma forma mais acurada de estimar associações de variáveis que são correlacionadas, como é caso dos escores de EPM e as variáveis da carcaça (Tabela 3), é através de análises multivariadas (SILVA et al, 2015;FERREIRA et al, 2018;OLIVEIRA et al, 2019a;OLIVEIRA et al, 2019b). Esta ferramenta estatística pode ser usada com sucesso para apoiar a tomada de decisão na escolha de variáveis que efetivamente contribuem para a elucidação do caráter alvo, que nesse caso, é a precocidade em fêmeas da raça Nelore.…”
Section: Resultsunclassified
“…Older animals were expected to show higher pH values, since they are usually more reactive than younger animals, depleting their muscle glycogen reserves faster. Although the statistical analysis did not compare males and females, on the average of the different maturities, females (5.54) showed higher pH values than males (5.51), which is probably due to the greater reactivity of the former in relation to males (5) . Working with zebu females divided into eight groups, Leite et al (28) found only one of these to be in the ideal pH range (below 5.8), which was due to the inappropriate management preslaughter, influencing the animal welfare parameters.…”
Section: Resultsmentioning
confidence: 91%
“…Simarly, the high number of bruises is due to the conformation of the animals, that present a higher fatness degree and have less space in vehicles and corrals, being more prone to being hit. Evaluating 15,002 carcasses of Nellore crossbred animals in Minas Gerais State and investigating the probable causative agents of bruises, Silva et al (5) found that injuries originate from several potential factors, and the subcutaneous fat score influences their occurrence, in which carcasses with higher fatness scores (> moderate) had more injuries when compared with carcasses whose fatness was scarce or absent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations